Legal Analysis of Criminal Responsibility of Revenge Porn Perpetrators in the Protection of Victims' Personal Data - Adil Nur, Muhammad Rifqi; Said, Muhammad Fachri; Mursyid , Mursyid (Faculty of Law, Universitas Muslim Indonesia, 2025)
The purpose of this study is to examine and analyze the applicable regulations and legal actions against perpetrators of revenge porn, as well as to examine and analyze the applicable regulations aimed at protecting the victims' personal data in revenge porn cases. This research is an empirical legal study with a legislative and case approach. The data collection techniques used are document study and interviews. Data analysis was conducted using descriptive qualitative methods. The results of the study are: Indonesia currently lacks specific legislation on revenge porn. Legally, perpetrators are penalized for violating laws related to the distribution of pornographic content and the victim's personal data. This study also identifies legal regulations that are used to protect the rights of victims as the harmed party in these cases. However, in practice, psychological rehabilitation of victims has not been well implemented. Rehabilitative resources are minimal, and typically, once a case is closed, victims are left unattended as they are assumed to be safe from further harm. Therefore, there is a need for laws that regulate revenge porn so that victim restitution rights can be properly followed up after a case is closed. The recommendations of this study are:Cases involving revenge porn should be handled with consideration of various factors to determine whether someone is guilty. Thus, there needs to be specific legal regulation regarding revenge porn itself. The handling of such cases often takes a long time, resulting in delayed removal of the victim's information, which may have already been spread widely online. This highlights the importance of having specific legal regulations on this issue, so that the justice and rights of victims can be fully realized.